A Royal Life Remembered - New Straits Times, (2008)
SELANGOR has a new museum and gallery which provides a fascinating glimpse into the history of the Selangor sultanate and the life and times of the eighth Sultan Sultan Salahuddin Abdul Aziz Shah.